2014
DOI: 10.21837/pmjournal.v12.i3.131
|View full text |Cite
|
Sign up to set email alerts
|

Residential Satisfaction - Concept, Theories and Empirical Studies

Abstract: Residential satisfaction, defined as the feeling of contentment when one has or achieves what one needs or desires in a house, is an important indicator and planners, architects, developers and policy makers use it in a number of ways. There are three theories – housing needs theory, housing deficit theory and psychological construct theory, and most empirical studies have used these theories or a combination of these theories in their research design. A number of variables representing housing and neighbourho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
9

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 3 publications
6
68
1
9
Order By: Relevance
“…It can be claimed Ardabil Mehr housing project has not been able to meet the demands of low-income people and Ardabil's Mehr buildings residents are not satisfied from their affordable houses. The result of this study is in contrast with obtained result of Karimzadeh, Shahriar, and Keshtkaran's study, that showed Abadeh and Sarvestan's residents problem has been solved by the affordable housing [14,15].…”
Section: Resultscontrasting
confidence: 96%
“…It can be claimed Ardabil Mehr housing project has not been able to meet the demands of low-income people and Ardabil's Mehr buildings residents are not satisfied from their affordable houses. The result of this study is in contrast with obtained result of Karimzadeh, Shahriar, and Keshtkaran's study, that showed Abadeh and Sarvestan's residents problem has been solved by the affordable housing [14,15].…”
Section: Resultscontrasting
confidence: 96%
“…In addition, Lovejoy, Handy [25], Bjorklund and Klingborg [26], and Parkes, Kearns [27] in their studies found that perception of safety was the most important contributing factor to residential satisfaction. The findings from the present study support the P-E fit theory, in which safety is an important determinant of residential satisfaction in general population and particularly in the elderly [14,20].…”
Section: Discussionsupporting
confidence: 84%
“…However, descriptive results from a representative sample of community-dwelling older adults aged 65 to 84 years in Madrid (Spain) showed a high degree of satisfaction with the residential environment [17]. It is worth mentioning that residential satisfaction varied from place to place and is significantly influenced by social-cultural values [20].…”
Section: Discussionmentioning
confidence: 99%
“…Dalam mengidentifikasi faktor yang mempengaruhi kepuasan tempat tinggal Mohit & Raja (2014) mendasarkan pada empat faktor yaitu (1) karakteristik sosial demografi penghuni yang dijabarkan menjadi variabel umur, pendapatan, lama tinggal, status kepemilikan, dan tipe rumah tangga; (2) karakteristik hunian meliputi variabel jumlah kamar tidur dan toilet, ukuran dan letak dapur, kualitas bangunan rumah; dan (3) karakteristik lingkungan sekitar meliputi variabel lokasi terhadap fasilitas umum seperti tempat kerja, sekolah, pusat kesehatan dan pusat perbelanjaan.…”
Section: Kepuasan Terhadap Tempat Tinggalunclassified